EMBARGO RIBA KONTEKS TRADISI KREDIT KENDARAAN DAN PELUANG EKSES NEGATIFNYA (Study Kasus Masyarakat Bone-Sulawesi Selatan dari 2000-2014) - Sumpeno Sumpeno (Institut Agama Islam Negeri Bone, 2020)
AbstractRente as a sistem transaction in human or nation life is once social dynamic. It was jargon in certen era. For example in Pra Islam in the nation of Arabic. The Rente was an economic traditional roll. Muhammad as a prophet success to embargo it for his power and his pollowes among of muslem in Madinah and Makkah. The rente’s embargo continioused by his pollowers from his deth antil to day. But in modern age, stap by stap, the spirit of the rente’s embargo is losing around of muslim commanded by al-Qur’an and al-Hadist those are forbidden’t Rente as a roll of sistem transaction in buying and selling. Why they do it ? After researching them, the writer found that the greate cause is come back to life stile and their life fhilosofy. With Siiri as the great cause, they did Rente while it was lossed some else. The Rente Sistem in their social economi dynamic, stap by stap will make them out of his country. Kata Kunci: Embargo; Riba; Tradisi; Kendaraan.